(untitled) (Bangladesh Journal of Agricultural Research, 2023)
The experiment was conducted at farmers’ field of Kamdebpur village under Nalchity upazila of Jhalakati district of Bangladesh during 2019-2020 and 2020-2021 to develop suitable management package for increasing the yield and quality of murta. The treatments comprised of five management practices on existing murta plants viz., T1 = Fertilizers (Inorganic + organic, 70-32-40 kg/ha N-P-K, respectively and compost 3 t /ha) + Pesticides application (on rhizome and plant parts) + Pruning (extra tillers and cleaning of dead plant parts), T2 = Fertilizers (inorganic + organic) + Pruning, T3 = Pesticides (insecticide + fungicide) + Pruning, T4 = Pruning and T5 = Farmers’ practice (without management). The experiment was set up on 10 years old existing mutra plant. The experiment was laid out in randomized complete block design with three replications. Plant height, doga height, doga diameter, single doga weight, fresh doga yield and rating of doga quality varied significantly due to different management practices. The maximum fresh doga yield (32.37 t/ha) was found in T1 treatment and it was statistically identical to that of T2 treatment (26.66 t/ha). In terms of rating of doga quality (considering length, colour and strength of murta cane), treatment T1 showed the highest quality (2.33) and it was at par to that of T2 and T3 treatments (3.33). The farmers’ practice showed the lowest quality doga (4.67), which was similar to that of T4 treatment (4.00). The results further revealed that treatment T1 increased the doga yield of 68.35% over the farmers’ practice. However, yield of doga for treatments T2, T3 and T4 treatments were 38.64, 31.38 and 14.97% higher over farmers’ practice, respectively. In terms of cost and return, treatment T1 gave the highest gross margin (Tk. 98765/ha), it was slightly reduced in T2 and T3 treatments (Tk. 67663 and 66086/ha, respectively). Improved agronomic practices enhanced the growth and quality of murta stem. Considering the stem (doga) yield, quality and economic return, fertilizers (Inorganic + organic, 70-32-40 kg/ha N-P-K, respectively and compost 3 t /ha) + Pesticides application (on rhizome and plant parts) + Pruning (extra tillers and cleaning of dead plant parts) would recommended for murta cultivation in Jhalakati. Bangladesh J. Agril. Res. 47(2): 205-213, June 2022